DIREITO DE MORTE E PODER SOBRE A VIDA: SABERES PARA O GOVERNO DOS CORPOS - Franciele Roberta Cordeiro; Maria Henriqueta Luce Kruse (Universidade Federal de Santa Catarina, Programa de Pós Graduação em Enfermagem, 2016)
This study aimed to examine how the media articulates the knowledge and positions involved in the process of death and dying. Documentary research in the field of post-structuralist cultural studies. The empirical material consisted of ten interviews, published in the magazines Época and Veja , between 2000 and 2012. To delimit the corpus of analysis, we used discursive mapping by means of the software ATLAS.ti. The findings were submitted to discourse analysis inspired by Foucault. In the reports, nursing appeared linked to care for the body and technical procedures, leading to the conclusion that the media constructs the professionals' image, according to the historical attributes linked to the professions. The knowledge of medicine and of justice is authorized to teach the subject to decide and to plan the death. Power/knowledge relations are outlined that legitimize the discourse on the production of a singularized death, which must be provided by the subjects using an expert of health.